(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The main objective of this research is to estimate the effect of exports on production in private manufacturing industry sector in Syria in the period between (1980-2010), using the Johansen test and VAR model, we have found that there is no significant impact of exports on production in private manufacturing industry sector neither in short run nor in long run.